Employee engagement for high firm performance: the case of lean six sigma at a Malaysia trading company / Hadijah Iberahim ... [et al.] - Iberahim, Hadijah; Azman, Izmahariz; Shahri, Mohd Haniff; Abdul Hamid, Nur Fara Ellyanie
Lean Six Sigma (LSS) is a method that helps an organization to maximize profit and minimize cost. One of the essential factors for a successful LSS project is the availability of employees who are willing to engage. Employee engagement brings about a strong sense of belonging and high productivity. Consequently, engaged employees will work harder to achieve the mission of the organization. This paper discusses a case of LSS project with a low level of employee engagement. As a result, LSS was less likely helpful in sustaining company's performance. The purpose of this study is to identify factors that contribute to employee engagement in LSS practices. Review of the relevant literature suggests four variables, which include goal clarity, management support and trust, knowledge sharing and transfer, and teamwork. The questionnaire survey applied census in collecting feedback from 80 respondents. Statistical analysis results indicate that goal clarity, management support, and trust are significant to employee engagement. However, knowledge sharing and transfer as well as teamwork are not substantial. It is recommended for the organization to give attention to all the four factors. This paper extended understandings on critical inputs to a successful implementation of LSS for sustainable company's performance and growth.